African Traditional Religion: A New Struggle for African Identity - Muyingi, Mbangu A. (The Asia Journal of Theology, 2015)
This article investigates the social status attributed to African Traditional Religion (ATR) in determining culture and identity. Since ATR is seen to be the sum total of the peculiarities shared by African people, African people’s values can also be seen as part of their identity. However, this article shows that the loss of African identity has raised numerous problems on the continent because of the marginalisation of ATR. According to Mbiti (1995:5), ATR plays a holistic role in an African’s understanding of his/her origin and purpose. A theoretical approach as to how ATR is the source of African identity is provided here. The study will argue that there is a need to rethink on the significance of ATR and the ontology that recognises it as part and parcel of African identity. By doing so, ATR can be revaluated, and its relevance established and sustained in order to give credence to authentic African identity.
Keywords: Africa – History; Africa.; Africans – Identity; Colonialism and neocolonialism; Culture and religion